Understanding Adventure Tourists’ Profile: A Case Study from Himachal Pradesh (India) - Chandel, Jyoti Kumar (Turizam, 2021)
Adventure tourism is one of the rapidly growing segments in the global tourism industry. Growth potential of adventure tourism has been realised in India, and tourism organizations are making consistent efforts to tap various opportunities evolving in this segment. Tourism organizations are continuously seeking to get better insights into the profiles of adventure tourists to formulate and execute strategies in an efficient and effective manner. Primary data for this study have been collected from 235 adventure tour participants and 230 adventure training participants through multi-stage sampling from the Indian state of Himachal Pradesh. Reported results of different dimensions of adventure tourists’ profiles offer better insights for tourism organizations.